2009
DOI: 10.1016/j.jjcc.2008.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Utility of rapid D-dimer measurement for screening of acute cardiovascular disease in the emergency setting

Abstract: Rapid measurement of D-dimer is useful for the screening of ACVD in the emergency setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…A recent study demonstrated that D-dimer using the cut-off value of 500 ng/ml showed a high sensitivity of 96.6% and a high negative predictive value of 97.6% [15]. However, D-dimer is also elevated in many diseases, such as pulmonary embolism [16,17], ACS [17][18][19], and stroke [20], which can and do mimic clinical presentation of AAD. If patients present to the ER with elevated D-dimer level and without typical clinical presentation of AAD, physicians may not perform diagnostic imaging studies.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study demonstrated that D-dimer using the cut-off value of 500 ng/ml showed a high sensitivity of 96.6% and a high negative predictive value of 97.6% [15]. However, D-dimer is also elevated in many diseases, such as pulmonary embolism [16,17], ACS [17][18][19], and stroke [20], which can and do mimic clinical presentation of AAD. If patients present to the ER with elevated D-dimer level and without typical clinical presentation of AAD, physicians may not perform diagnostic imaging studies.…”
Section: Discussionmentioning
confidence: 99%
“…21 Moreover, Tokita et al found that D-dimer showed significantly higher positive test rate for the detection of ACS in the very early phase compared with troponin T and therefore they concluded that the D-dimer was regarded useful for the screening of ACS in the emergency setting. 22 In contrast, Itakura et al reported that D-dimer did not distinguish patients presenting with AMI from those with stable angina. 19 Another 2 large prospective studies suggested that D-dimer did not aid detection of ACS or predict prognosis above and beyond established risk factors.…”
Section: Value Of D-dimer As a Predictor Of Severity In Cadmentioning
confidence: 95%
“…In 257 patients with chest pain, raised D-dimer had an independent diagnostic value for AMI (positive and negative predictive values estimated as 92% and 41%, respectively) and increased the diagnostic sensitivity of the electrocardiogram and history from 73% to 92% (47). In another study of 279 patients with suspected ACS, D-dimer showed significantly higher positive test rate for the detection of ACS in the very early phase compared with troponin T and therefore was regarded useful for the screening of ACS in the emergency setting (48). In the ADVANCE Study, however, D-dimer did not distinguish patients presenting with AMI from those with stable angina (38).…”
Section: D-dimermentioning
confidence: 96%